Επισκόπηση Ευρωπαϊκών Αγορών Ενέργειας: - Papadimoulis, Faidon (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2014)
Energy as a commodity and economic figure constitutes one of the most discussed issues in the contemporary world containing under that “umbrella term” some of the most compelling questions of our time. Ranging from the finite character of fossil fuels along with the respective development paradigm, the environmental impact of energy production even in some considered innocent forms like hydroelectricity, the geostrategic independence of greater regions, to social issues like energy poverty, sustainability or the use of nuclear power, energy and the subcategory of energy economics are a developing academic area aspiring to provide useful answers or at least tools to advocate them in favor of well-planned solutions. This dissertation has the ambition to address some of those issues with main target to assess the impact on inflation imposed by the change in energy prices among all (27) EU member countries and to evaluate the process and rate of homogenization in the European Union by utilizing statistical tools. In the first chapter a general introduction of the subject is presented by explaining some key energy figures and the reasons of utilization of open public data and statistical methods. In the second chapter a presentation of the EU countries’ energy market, infrastructure and framework is taking place, which will be used afterwards. In the third chapter are presented the results of the statistical software package for the impact on inflation caused by energy prices, as well as attempts of interpreting that figure. In the fourth chapter are presented the regression lines and the computations for the rise in energy prices’ time series and their associations especially with international oil prices’ trend. In the fifth chapter we used clustering methods for classifying the EU members in two different points of time by using both quantitative and qualitative figures and attributes and then we compared the level of similarity. In the sixth chapter are expressed the final conclusions of this dissertation regarding the homogenization target set by the EU as step for the further economic unification. For the elaboration of the dissertation were used solely public data, maintained and published by institutions and services of the European Union or of its member states. The statistical software used was Minitab and XLSTAT.